Development of Transgenic Papaya through Agrobacterium-Mediated Transformation - Md. Abul Kalam Azad; Md. Golam Rabbani; Latifah Amin; Nik Marzuki Sidik (International Journal of Genomics)
Transgenic papaya plants were regenerated from hypocotyls and immature zygotic embryo after cocultivation with Agrobacterium tumefaciens LBA-4404 carrying a binary plasmid vector system containing neomycin phosphotransferase (nptII) gene as the selectable marker and β-glucuronidase (GUS) as the reporter gene. The explants were co-cultivated with Agrobacterium tumefaciens on regeneration medium containing 500 mg/L carbenicillin + 200 mg/L cefotaxime for one week. The cocultivated explants were transferred into the final selection medium containing 500 mg/L carbenicillin + 200 mg/L cefotaxime + 50 mg/L kanamycin for callus induction as well as plant regeneration. The callus derived from the hypocotyls of Carica papaya cv. Shahi showed the highest positive GUS activities compared to Carica papaya cv. Ranchi. The transformed callus grew vigorously and formed embryos followed by transgenic plantlets successfully. The result of this study showed that the hypocotyls of C. papaya cv. Shahi and C. papaya cv. Ranchi are better explants for genetic transformation compared to immature embryos. The transformed C. papaya cv. Shahi also showed the maximum number of plant regeneration compared to that of C. papaya cv. Ranchi.